(untitled) (EDUCATION IN THE 21ST CENTURY, 2023)
The social and economic transformation of the late 20th century and the early 21st century, the powerful impact of globalization directly influenced the structure and role of almost all social institutions, including the social institution "Family"., that may become the key domestic clashes, violence in This context, the topic is important, because bean is a very important issue that concerns family violence, in particular in respect of the child violence cases the problem involved is interested in both domestic and foreign experts, which touched against a child, abuse several classifications (Harutyunyan K., Galstyan M.; Alekseeva L., Tseluyko V., Sorokin P., Radbill S.): Physical violence, Sexual violence, Contempt, Psychological violence, Economic violence. These are difficult socio-economic conditions, unemployment, stereotype of national consciousness, rough character, uncompromising, selfishness, disagreement in the issue of child upbringing, alcohol abuse, drug addiction, psychological violence, etc: Until recently, the problem was regulated in the sub-legislative field, providing inadequate and unfair solutions. but only the activities of NGOs were not enough to effectively solve the problem. In 2017 - fortunately, the RA Law on this issue was adopted, which ensured the safety of persons subjected to violence, in particular, children, based on the interests of the child. Although the RA law controls and regulates the field, it is the duty of each of us, society and the state to take care of children, protect their rights, educate and educate them without any violence, being well aware that today’s child is our future.